A novel allele, HLA‐DPA1*01:87Q identified by next generation sequencing. (21st October 2021) - Liacini, Abdelhamid; Peters, Lindsey; Gravante, Christopher; Pfau, Kimberly; Geier, Steven
Abstract : A point mutation in Exon 1, 1‐3 (ATG>ACG) causes a non‐synonymous change to the start codon, which may affect expression.